2010
DOI: 10.1111/j.1365-3059.2010.02328.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in carbohydrate metabolism in Citrus sinensis infected with ‘Candidatus Liberibacter asiaticus’

Abstract: Changes in carbohydrate metabolism in sweet orange (Citrus sinensis) infected with 'Candidatus Liberibacter asiaticus', a purported cause of citrus Huanglongbing (HLB), were investigated. Starch levels in HLB-infected leaves with and without symptoms increased 3AE1-and 7AE9-fold, respectively, compared to healthy controls. In symptomless leaves, sucrose and fructose accumulated significantly (P < 0AE05) in both midribs and lobes, and glucose only in the midribs (greater than fivefold); whereas maltose levels w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
100
1
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(119 citation statements)
references
References 30 publications
11
100
1
7
Order By: Relevance
“…However, further analysis of sugar concentrations will be necessary to clarify the causes and effects of disease symptoms in the fruit. Other studies on CaLas-infected leaves have shown increased sucrose and glucose, but not fructose [37]. In fruit, it is possible that altered fructose and glucose concentrations might be responsible for physiological disorders and affect source-sink relationships with leaves.…”
Section: Discussionmentioning
confidence: 91%
“…However, further analysis of sugar concentrations will be necessary to clarify the causes and effects of disease symptoms in the fruit. Other studies on CaLas-infected leaves have shown increased sucrose and glucose, but not fructose [37]. In fruit, it is possible that altered fructose and glucose concentrations might be responsible for physiological disorders and affect source-sink relationships with leaves.…”
Section: Discussionmentioning
confidence: 91%
“…One of the major physiological disorders of citrus caused by HLB disease has been reported to be the massive starch accumulation in leaf and stem tissues due to aberrant carbohydrate metabolism and phloem blockage (57,58). The tissues surrounding the fruit abscission zone are rich in vascular tissue where starch accumulation was found in HLB-affected citrus.…”
Section: Discussionmentioning
confidence: 92%
“…Altered expression of these genes can cause abnormal circadian rhythms which, in turn, result in disorders of clock-regulated pathways, such as photosynthesis, transport of sugars, and starch metabolism (Harmer et al 2000). Interestingly, repression of photosynthesis pathway genes and disorders of carbohydrate metabolism (genes and metabolites) have been observed in HLB-affected sweet orange (Albrecht and Bowman 2008;Fan et al 2010Fan et al , 2011. It is suggested that the transcriptional changes of these MYB-related transcription factors may correlate to the interference of photosynthesis and carbohydrate metabolism in 'Ca.…”
Section: Significantly Hlb-modulated Pathways At Each Time Pointmentioning
confidence: 98%